One-dimensional flat bands in twisted bilayer germanium selenide - D. M. Kennes (Nature Portfolio, 2020)
Twisting the relative orientation of the sheets in few-layer van der Waals materials can cause drastic changes in the electronic bandstructure. Here, the authors predict that twisted bilayer GeSe realises an effective one-dimensional flat-band electronic system with exotic, strongly correlated behaviour.